Penapisan dan Karakterisasi Amilase dari Bakteri Asal Ekoenzim - Ninda Ningtyas; Nisa Rachmania Mubarik; Mulyorini Rahayuningsih (Institut Pertanian Bogor, 2023)
Eco-enzymes are one of the potential sources for obtaining amylolytic bacterial isolates. The study aims to screen amylolytic bacteria from eco-enzymes, characterize semi-purification amylase, and identify amylolytic bacteria molecularly using the 16S rRNA gene. Screening for amylolytic bacteria was carried out by measuring the amylolytic index on a Nutrient agar medium containing 1% tapioca starch. The amylolytic isolate which had the highest index and was non-pathogenic was selected for the amylase characterization process. Testing of amylase activity was carried out using the Bernfeld method while the protein enzymes were measured using the Bradford method. The extracellular extract was concentrated using ammonium sulfate precipitation. PKL2 is gram-positive bacteria that was derived from eco-enzymes with the highest amylolytic indexes of 1.77, which were not pathogenic on the blood agar test. Optimum amylase was produced by PKL2 at the stationary phase at 21 h. The optimum pH and temperature of the amylase activity were observed to be 7.0 and 50°C, respectively. The amylase enzyme from PKL2 increased its purity 1.82-fold upon precipitation of ammonium sulfate at a concentration of 60%. Identification of bacteria based on molecular identification showed that PKL2 obtained was putatively identified as Bacillus amyloliquefaciens. Keywords: Amylase activity, Bacillus amyloliquefaciens, eco-enzyme, optimum pH